Fiche technique de l’impact de l’amendement du substrat en poudre de coquille d’œuf de poule sur la reproduction de Archachatina marginata (Swainson, 1821) - Baptiste, Aman Jean; Didier, Memel Jean; Daniel, Kouassi Kouadio; Atcho, Otchoumou (European Scientific Journal, ESJ, 2018)
This study consists in looking for an improvement of Archachatina margina reproductions performances by amendment of the breeding substrates. As a result, five types of substrate were prepared by soil amendment at different rates (0%, 10%, 20%, 30% et 40%) with chicken egg shell powder. On these substrates, snails were raised from spat stage until they were laid. Reproductive parameters such as: age of first laying, the number of annual laying per animal, the number of eggs per laying on the different substrates were recorded. Overall, snail laying performances improved with increasing rate of substrate amendment. However, beyond a rate of 20%, the weight of eggs laid began to decline. The chicken egg shell powder is suitable for the amendment of the breeding substrate of snails Archachatina marginata in view of an improvement in their reproductive performance. The rate of amendment recommended to this effect is 20%.